2018
DOI: 10.1002/admt.201800535
|View full text |Cite
|
Sign up to set email alerts
|

Precise Network Polymerized Ionic Liquids for Low‐Voltage, Dopant‐Free Soft Actuators

Abstract: Next‐generation material applications require electroactive materials for actuation which are light weight, operate at low voltages (<5 V), exhibit cyclability, and are compatible with a range of environments. Here, a class of network polymerized ionic liquid (n‐PIL) actuators is reported, synthesized via a facile step growth polymerization, which not only have comparable actuation strains (≈0.9%) to other state‐of‐the‐art ionic polymer systems at ±3 V, but also exhibit 85% performance preservation after 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
34
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(34 citation statements)
references
References 53 publications
0
34
0
Order By: Relevance
“…Here d is the tip displacement in horizontal direction, L is the free length of the film and w is the thickness of the strip with electrodes . As plotted on the right axis of Figure c, the overall bending strain in our hybrid aligned iLCE is about 0.3%, comparable to iEAPs …”
mentioning
confidence: 87%
“…Here d is the tip displacement in horizontal direction, L is the free length of the film and w is the thickness of the strip with electrodes . As plotted on the right axis of Figure c, the overall bending strain in our hybrid aligned iLCE is about 0.3%, comparable to iEAPs …”
mentioning
confidence: 87%
“…For instance, Shen et al synthesized a crosslinked poly(ionic liquid) with an imidazolium backbone and bis(trifluoromethane sulfonimide) counterions. 163 An electro-responsive actuator was further designed by implementing this as-synthesized poly(ionic liquid) between two carbon nanotube sheets. The resulting actuator bent on applying a voltage as a result of charge accumulation on one of the carbon nanotube sheets due to ion transport.…”
Section: Ionic Conductivitymentioning
confidence: 99%
“…[ 72,73 ] Similar trends have been observed in TFSI − single anion conducting network systems. [ 16,74 ] At 8 mol% crosslinking and below, the conductivity is essentially invariant, while a 24 mol% crosslinker sample begins to show a reduction. A normalized plot superposes the data as shown in Figure S7 indicating this is primarily a T g effect.…”
Section: Resultsmentioning
confidence: 99%
“…Polymer networks containing ionic species have received attention as functional materials in liquid/gas separations, [9][10][11][12][13][14][15] soft actuators, [16][17][18][19][20] ion exchange membranes, [21][22][23][24][25] and electrolytes for energy storage. [26][27][28][29][30][31][32][33][34][35] In the context of lithium conduction, polyethylene oxide (PEO) networks with added lithium salts have been investigated and it was shown that covalent crosslinking can significantly reduce the crystallinity and increase the ionic conductivity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation